The effects of oil price and US economy on Thailands macroeconomy: the role of monetary transmission mechanism - Razmi, Fatemeh; Mohamed, Azali; Lee, Chin; Habibullah, Muzafar Shah (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This article investigates the channels of monetary transmission mechanism alongside oil price and the US industrial production, as two causes of recent crisis, during the pre-and post-crisis of 2007-2009 in thailand. the channels of monetary transmission mechanism barely have an effect on consumer price index and industrial production while oil price strongly affects both industrial production and consumer price index and the US industrial production robustly influences consumer price index during pre-crisis. However, oil price and the US industrial production greatly lose their effects on consumer price index and industrial production after the crisis period, the oil price is still mostly explains the variation of the consumer price index. The stock price is most effective conduit for monetary policy to industrial production during post-crisis period.